Modelling and predicting the quality of Cheddar cheese during ripening - Chen, Yangyi (2020)
Cheddar cheese maturation is crucial during cheese manufacture producing distinct flavours and textures. However, it is a slow and expensive process and also not all of the cheese production is capable of reaching the highest quality. Therefore, predictive tools are necessary to allow the optimisation and consistency of supply of mild-mature/vintage Cheddar cheeses, minimising losses.